PERCEPT myeloma: a protocol for a pilot randomised controlled trial of exercise prehabilitation before and during autologous stem cell transplantation in patients with multiple myeloma. Issue 1 (29th January 2020) - McCourt, Orla; Fisher, Abigail; Ramdharry, Gita; Roberts, Anna L; Land, Joanne; Rabin, Neil; Yong, Kwee
Abstract : Introduction: Myeloma, a blood cancer originating from plasma cells, is the most common indication for autologous stem cell transplantation (SCT). Patients with myeloma undergoing autologous SCT (ASCT) experience treatment-related morbidity and reduction in function and well-being for many months post-treatment. Interventions targeting physical functioning delivered prior to and during SCT have shown promising results in mixed haematological populations and may offer a non-pharmacological solution to physically optimising and preparing patients for SCT. The aim of this study is to investigate the feasibility of a physiotherapist-led exercise intervention as an integral part of the myeloma ASCT pathway at a UK tertiary centre. Methods and analysis: PERCEPT is a single-site, pilot randomised controlled trial of an exercise intervention embedded within the myeloma ASCT pathway, compared with usual care. The primary study end points will be feasibility measures of study and intervention delivery including recruitment rates, acceptability of intervention, study completion rate and any adverse events. Secondary end points will evaluate differences between the exercise intervention group and the usual care control group in cancer-related fatigue, quality of life, functional capacity (6 min walk test; handheld dynamometry; a timed sit-to-stand test) and objective and self-reported physical activity. Outcomes will be assessed at four time points, approximately 6–8 weeks prior to SCT, on/around day of SCT, on discharge from SCT hospital admission and 12 weeks post-discharge. The exercise intervention comprises of partly supervised physiotherapist-led aerobic and resistance exercise including behaviour change techniques to promote change in exercise behaviour. The primary outcomes from the trial will be summarised as percentages or mean values with 95% CIs. Group differences for secondary outcomes at each time point will be analysed using appropriate statistical models. Ethics and dissemination: This study has NHS REC approval (Camden and Kings Cross, 19/LO/0204). Results will be disseminated through publication and presentations at haematology and rehabilitation-related meetings. Trial registration number: ISRCTN15875290 .